From covid war to cold war : the new three-body problem (2020)
I n Liu Cixin’s extraordinary science fiction novel The Three-Body Problem, China recklessly creates, then ingeniously solves, an existential threat to humanity. During the chaos of Mao Zedong’s Cultural Revolution, Ye Wenjie, an astrophysicist, discovers the possibility of amplifying radio waves by bouncing them off the sun and in this way beams a message to the universe. When, years later, she receives a response from the highly unstable and authoritarian planet Trisolaris, it takes the form of a stark warning not to send further messages. Deeply disillusioned with humanity, she does so anyway, betraying the location of Earth to the Trisolarans, who are seeking a new planet because their own is subject to the chaotic gravitational forces exerted by three suns (hence the book’s title). So misanthropic that she welcomes an alien invasion, Ye cofounds the Earth-Trisolaris Organization as a kind of fifth column, in partnership with a radical American environmentalist named Mike Evans. Yet their conspiracy to help the Trisolarans conquer Earth and eradicate humankind is ingeniously foiled by the dynamic duo of Wang Miao, a nanotechnology professor, and Shi Qiang, a coarse but canny Beijing cop.1